The Effect of Accounting Knowledge and Education Level on MSME Performance with Understanding of SAK EMKM as an Intervening Variable - Robir Rahmat Putra; Syaka Nur Khalisa (Cakrawala Repositori IMWI, 2023)
This study aims to examine and analyze the effect of accounting knowledge and educational level on the performance of MSMEs with an understanding of SAK EMKM as an intervening variable. The sample in this study was 189 respondents, who are SMEs in the area around DKI Jakarta, especially North Jakarta. Adequacy of the number of respondents based on the approach used by Hair. The data collection technique used simple random sampling by distributing research questionnaires in the form of Google forms and then distributing them to MSME actors through social media. The data processing method in this study uses the Smart PLS (Partial Least Square) software which is used to test the hypothesis. The results of this study indicate that accounting knowledge has no effect on MSME performance, accounting knowledge has a positive and significant effect on understanding SAK EMKM, education level has a positive and significant effect on MSME performance, education level has a positive and significant effect on understanding SAK EMKM, understanding SAK EMKM is proven to have no effect on MSME performance, accounting knowledge is proven not to affect MSME performance indirectly through understanding SAK EMKM, education level is proven not to affect MSME performance indirectly through understanding SAK EMKM. The results of this study recommend that MSME actors if they want to improve the performance of the MSME they run, MSME actors must study accounting so they can apply SAK EMKM to managing their financial reports.